2022
DOI: 10.3390/ijerph19031759
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Child’s Health in Pakistan and the Moderating Role of Birth Spacing

Abstract: There is a consensus that better health should be viewed both as both a means and an end to achieve development, and the level of development should be judged by the health status of the population and the fair distribution of health services across the people. Many determinants affect a child’s health. This study aimed to explore a child’s health predictors and the moderating role of birth spacing on the association between mother’s health care services utilization (MHCSU) and a child’s health. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…A positive correlation exists between a mother’s age and her child’s health. Older mothers use maternal health care services more frequently and their infants are healthier than those of younger mothers [ 28 , 29 , 30 , 31 , 32 , 33 ]. It is to be noted that parental education and a child’s health are positively associated.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation exists between a mother’s age and her child’s health. Older mothers use maternal health care services more frequently and their infants are healthier than those of younger mothers [ 28 , 29 , 30 , 31 , 32 , 33 ]. It is to be noted that parental education and a child’s health are positively associated.…”
Section: Discussionmentioning
confidence: 99%
“…Further, 53 studies were specific to short birth interval and reported on either the prevalence or the predictors and 87 studies were not specific to short birth interval but considered birth interval as a covariate (Table S6 in the Online Supplementary Document). Characteristics of the studies that followed the WHO recommendation [14,17,[36][37][38][39][40][41][42][43][44] for the definition and classification of short birth interval are presented in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…In the studies that measured birth-to-birth interval and classified a birth interval of <24 or ≤24 months as a short birth interval (n = 23), the prevalence of short birth interval ranged from 5.1 [69] to 64.4% [70]. In the studies that measured birth-to-birth interval and considered a birth interval of <18 months as a short birth interval (n = 7), the reported prevalence ranged from 1.3 [71] to 42.5% [72]. For studies that measured birth-to-birth interval and considered a birth interval of <33 or ≤33 months as a short birth interval (n = 10), the reported prevalence ranged from 17.4 [38] to 72.7% [73].…”
Section: Prevalence Of Short Birth Intervalmentioning
confidence: 99%
“…In Pakistan, the mCPR remains low, at less than 3% for implants and IUCD [9]. Client-centered counseling has proven to be a successful approach if implemented with the intention of understanding community needs and involves a continuous learning process to adopt field lessons [23][24][25]. Our model and implementation strategy stand uniquely for the setting.…”
Section: Plos Onementioning
confidence: 99%